New Perspectives on the Impact of Iron Chelation Therapy on the Gut Microbiome in Thalassemia Patients - Sara Deumić; Neira Crnčević; Mirsada Hukić; Muamer Dizdar; Monia Avdić (Thalassemia Reports)
Thalassemia, a genetic condition characterized by defective hemoglobin synthesis, is often managed with transfusion therapy, which can lead to iron overload—a significant contributor to morbidity and mortality due to organ damage and pathogenic infections. Iron chelation therapy, the cornerstone of managing iron toxicity, may inadvertently influence the gut microbiome, a critical modulator of immunity and metabolism. This review provides new insights into the interplay between iron chelation therapy and gut microbiome dynamics in thalassemia patients. It synthesizes findings on how chelators such as deferoxamine, deferasirox, and deferiprone influence microbial composition, iron availability, and systemic inflammation. Emerging evidence highlights alterations in gut microbial diversity, with reduced beneficial taxa and increased pathogenic populations, driven by changes in luminal iron levels. This imbalance contributes to immune dysregulation, systemic inflammation, and susceptibility to infections. The review advocates for tailored treatment strategies that integrate microbiome-targeted interventions alongside traditional chelation therapy to improve patient outcomes. By combining genetic profiling, dietary adjustments, and microbiome modulation, this approach offers a promising avenue for personalized medicine in thalassemia care.